2017
DOI: 10.1177/1747954117727809
|View full text |Cite
|
Sign up to set email alerts
|

Salary differences under the salary cap in Major League Soccer

Abstract: Professional soccer is the world's most popular sport; a number of National Leagues are under the control of National Associations. The economic theory behind soccer is the continuing competition to earn much more than other sports do in the sports market. Since the supply of talent is limited, teams' demand for certain professionals is so strong that it leads to salary differences between players. Therefore, in this study, attention is given to the determinants of the differences in workers' salaries in the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Player position is another potentially important determinant of salary. 6 The goal-keeper position was eliminated from the data set because the position dummies in the model control for the goal-scoring and goal productivity of the player. Thus, a position dummy (whether a player is a forward or not) was included in the model.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Player position is another potentially important determinant of salary. 6 The goal-keeper position was eliminated from the data set because the position dummies in the model control for the goal-scoring and goal productivity of the player. Thus, a position dummy (whether a player is a forward or not) was included in the model.…”
Section: Methodsmentioning
confidence: 99%
“…This observation is supported by data from the MLS as well. After examining over 10 years of salary information, Celik and Ince-Yenilmez 6 reported that offensive players averaged a higher salary than defensive players. Accordingly, the following hypothesis is proposed: H 2 : A player rostered as a forward will have a higher base salary than non-forward field players.Along with position, player age may impact salary.…”
Section: Player Characteristics On Salarymentioning
confidence: 99%
See 3 more Smart Citations